2020
DOI: 10.3389/fvets.2020.00630
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Identification of Babesia spp., Theileria spp., and Anaplasma spp. in Sheep From Border Regions, Northwestern China

Abstract: Babesia, Theileria, and Anaplasma are important causative agents of tick-borne diseases that severely affect sheep. However, there is paucity in the occurrence genetic diversity of the infections of tick-borne diseases in sheep in border regions, northwestern China. In this study, nested polymerase chain reaction (nPCR) assays and gene sequencing were used to identify tick-borne Babesia spp., Theileria spp., and Anaplasma spp. infections in border regions, northwestern China. Out of 323 samples tested in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…This study confirms that both A. phagocytophilum and A. bovis can infect yaks. The infection rate of A. phagocytophilum in yaks (29.4%) in this study was higher than that reported in sheep (9.9%), dairy cattle (12%), and white yaks (5.3%) in other areas of China (1,13,37), and lower than that in C. pygargus (33.3%) from Heilongjiang China (17). Since the first case of HGA, caused by A. phagocytophilum, was reported in Anhui, China (38), HGA has been reported in the USA, Europe, Africa, and Asia (11,39,40).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This study confirms that both A. phagocytophilum and A. bovis can infect yaks. The infection rate of A. phagocytophilum in yaks (29.4%) in this study was higher than that reported in sheep (9.9%), dairy cattle (12%), and white yaks (5.3%) in other areas of China (1,13,37), and lower than that in C. pygargus (33.3%) from Heilongjiang China (17). Since the first case of HGA, caused by A. phagocytophilum, was reported in Anhui, China (38), HGA has been reported in the USA, Europe, Africa, and Asia (11,39,40).…”
Section: Discussioncontrasting
confidence: 80%
“…Currently, A. phagocytophilum, A. capra, and E. chaffeensis have been recognized as causative agents of human infection. Mixedinfection of tick-borne pathogens has also been observed in animals in other countries and regions (1,30,34,53). Above all, co-infection of tick-borne pathogens emphasizes the need for differential diagnosis of these pathogens in animal hosts and humans to improve the prevention and control of TBDs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(BILGIN et al, 2017), and China 63.8% for Anaplasma ovis and between 5 to 18.6% for Babesia sp. (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ticks are obligate haematophagous ectoparasites that can transmit several pathogens to humans and animals (Brites‐Neto et al., 2015; Dabaja et al., 2017; Merino et al., 2013; Peter et al., 2005). Among these pathogens, Babesia , Theileria and Anaplasma infections represent in sheep a real health problem in several regions of the world (Aydin et al., 2013; Iqbal et al., 2013; Li et al., 2020; Ozubek & Aktas, 2017). The epidemiology of these infections is dramatically influenced by abiotic factors, mainly temperature and humidity (Borşan et al., 2020; Estrada‐Pena, 2009).…”
Section: Introductionmentioning
confidence: 99%